2023
DOI: 10.1007/s10340-023-01604-w
|View full text |Cite
|
Sign up to set email alerts
|

Visual modelling can optimise the appearance and capture efficiency of sticky traps used to manage insect pests

Abstract: Sticky traps are one of the most important tools for monitoring and mass trapping of insect pests. Their effectiveness depends on attracting and capturing target pests efficiently. Trap colour strongly affects capture rates, but currently a principled approach to identifying optimal trap colour for a given pest and growing context is lacking. Here we propose that modelling pest colour vision enables identification of trap colours that optimise pest capture rates. We test this novel approach to trap design in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…This supports the hypothesis that attractiveness will be optimized when blue colours maximally stimulate blue photoreceptors while minimally stimulating green photoreceptors (Dearden et al, 2023).…”
Section: However Attraction Through Visual Signals Usually Occurs Onl...supporting
confidence: 79%
See 1 more Smart Citation
“…This supports the hypothesis that attractiveness will be optimized when blue colours maximally stimulate blue photoreceptors while minimally stimulating green photoreceptors (Dearden et al, 2023).…”
Section: However Attraction Through Visual Signals Usually Occurs Onl...supporting
confidence: 79%
“…Colour contrast also plays a crucial role in the localization and identification of suitable hosts for numerous fruit-eating and frugivorous insects (Burns & Dalen, 2002;Schaefer et al, 2006;Schmidt et al, 2004;Teixeira et al, 2010). Encouraging results have been observed when assessing visual stimuli in contrast to the background colour for WFT attraction (Dearden et al, 2023;Mainali & Lim, 2010;. It has also been reported that adding 200-400 μg of neryl (S)-2-methylbutanoate (aggregation pheromone) to blue and yellow traps increased capture rates by 2.5-3 times compared to the same traps without bait (Cruz-Esteban et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In one experiment conducted in England, traps baited with ( S )-(-)-verbenone significantly caught more thrips than traps baited with the solvent, whereas, in a second experiment conducted in Turkey, the results of the same odor treatment could be hardly distinguished from the solvent control [ 45 ]. Recently, a commercial lure, namely Thrips Charm ® , a mixture of p -anisaldehyde and ( S )-(-)-verbenone significantly increased catches from visual traps in the field [ 46 ]. No details about the ratio of both compounds in the commercial lure could be found.…”
Section: Discussionmentioning
confidence: 99%